On reachability and controllability for a Volterra integro-dynamic system on time scales - Santos, Iguer Luis Domini dos [UNESP]; Tikare, Sanket (Babes-Bolyai University Cluj-Napoca, 2025)
The paper studies and relates the notions of reachability and controllability for the Volterra integro-dynamic system on time scales. More specifically, we obtain necessary and sufficient conditions for reachability and controllability. In addition, we obtain an equivalence between the concepts of reachability and controllability studied.
Keywords: controllability; integro-dynamic equations; Reachability; time scales